2019
DOI: 10.1108/mrr-02-2018-0089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trainee characteristics, training attitudes and training need analysis on motivation to transfer training

Abstract: Purpose Trainees’ motivation to transfer the training imparted is an important constituent in determining required training outcomes in organizations. The purpose of this study is to examine the effects of trainee characteristics, training attitudes and training need analysis on motivation to transfer training. Design/methodology/approach Research hypotheses were tested using a survey. A questionnaire was used to collect data from employees of an Indian governmental power transmission organization, attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 94 publications
(138 reference statements)
2
34
0
4
Order By: Relevance
“…A three-item scale was adapted from Sahoo and Mishra (2019). The items included here were as follows: there is a formal mechanism to capture an employee's training needs; employees are nominated to attend training programs based on carefully identified training needs.…”
Section: Training Need Analysismentioning
confidence: 99%
“…A three-item scale was adapted from Sahoo and Mishra (2019). The items included here were as follows: there is a formal mechanism to capture an employee's training needs; employees are nominated to attend training programs based on carefully identified training needs.…”
Section: Training Need Analysismentioning
confidence: 99%
“…Therefore, learning transfer in this study emphasizes the combination of retention and generalization to ensure transfer of learning can occur effectively thereby improving the performance of individuals and organizations. Sahoo & Mishra (2019) and Singh (2017) stressed that the trainee's characteristic is a very critical factor to make learning transfer more effective. This is also support by the previous studies which stated that the characteristics of trainees are important factors and increase the effectiveness of learning transfer (Baldwin et al, 2017;Ford et al, 2018).…”
Section: Learning Transfermentioning
confidence: 99%
“…Corporate HR managers worldwide must feel that local HR managers are a part of a more extensive overall so-called global corporate HR network. Researchers have found that companies are involved in some of the most influential HR systems development practices in the world (Sahoo & Mishra, 2019). The most critical factor for achieving success is creating a worldwide custom infrastructure used to support, purchase, organize local activities to help better understand their systems and the challenges they face.…”
Section: Training Sdm Internationalmentioning
confidence: 99%